Pengaruh Digital Eco-Labels terhadap Kesediaan Konsumen Membayar Harga Lebih Mahal pada Marketplace - Nulthazam Sarah; Nur Fadilah Ayu Sandira; Indri Iswardhani; Sri Astuti Nasir (Lembaga Pengembangan Kinerja Dosen, 2026)
The proliferation of digital commerce platforms has transformed consumer behavior while simultaneously elevating environmental consciousness among Indonesian consumers. This research investigates the influence of digital eco-labels on consumer willingness to pay premium prices on marketplace platforms, specifically Shopee and Tokopedia, within Indonesian urban contexts. Employing a quantitative associative research design, this study collected data from 50 active marketplace users through purposive sampling techniques using structured questionnaires with five-point Likert scales. Multiple linear regression analysis was conducted to examine the relationships between digital eco-labels and willingness to pay premium prices, with perceived credibility and environmental knowledge as moderating variables. The findings reveal that digital eco-labels significantly and positively influence willingness to pay premium prices with a beta coefficient of 0.438 and significance level of 0.000. Perceived credibility effectively moderates this relationship with a coefficient of 0.312, while environmental knowledge demonstrates a moderating effect with a coefficient of 0.276. The research model explains 64.7 percent of the variance in willingness to pay premium prices. These empirical results confirm the applicability of Theory of Planned Behavior and signaling theory in the context of sustainable digital consumption in Indonesia. The study contributes theoretical insights into green consumer behavior within emerging market e-commerce platforms and provides practical implications for marketplace operators to develop transparent third-party verification systems for eco-labels, integrate educational content regarding sustainability, and optimize search algorithms to enhance visibility of verified sustainable products. Policy implications emphasize the necessity for governmental regulation standardizing digital sustainability labels and monitoring environmental claims in e-commerce to prevent greenwashing practices.